The Impact of the Formation of Malaysia 16 September 1963: A Historical Highlight - Ayu Nor Azilah Mohamad; Wayu Nor Asikin Mohamad; Abdul Razak Salleh; Mohamed Ali Haniffa (RIRAI Publisher, 2020)
This article discusses the impact of Malaysia's formation on September 16, 1963. The establishment of Malaysia involves Malaya, Sabah, Sarawak and Singapore. Planning at the early stage includes Brunei but the State withdrew at the end of Malaysia's formation. Singapore also dropped out from the Malaysia Formation two years later in 1965. The formation of Malaysia has affected Malaysia to this day. The objective of the study is to discuss the benefits of politics, socialization and racial relations in Malaysia. Among the things discussed in this article are the benefits of the platform of socialisation and racial relations in Malaysia as well as the political aspects. Both of these were examined using historical approaches and library research. The findings show that Malaysia's establishment has made Malaysia a unique nation with racial diversity. This includes the establishment of many political parties based on their respective race or tribe, especially in Sabah and Sarawak. All Malaysians enjoy the benefits of Malaysia’s establishment for harmony and peace.